Effects of plasma chemistry on the interfacial performance of protein and polysaccharide in emulsion. (April 2020) - Jiang, Yu-Han; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: Background: The interfacial performance of protein and polysaccharide plays a vital role in the improvement of food quality. As an innovative technology in food processing, cold plasma has attracted much attention from researchers and has become an attractive tool for nonthermal food processing due to the abundant reactive species generated at low temperatures. In particular, cold plasma shows great potential in food component modification. However, some of the specific physical-chemical reactions between reactive species in plasma, and protein and polysaccharide still remain obscure, limiting the development of accurate modification. Scope and approach: This review provides an overview of the effects that plasma makes on the interfacial performance of protein and polysaccharide in the emulsion. Aspects discussed include types of active species in cold plasma, detailed interaction between reactive species, and protein and polysaccharide, and changes of interfacial properties. In addition, the current review presents a summary of the modification of protein and polysaccharide resulting from cold plasma application. Key findings and conclusions: The reactive species produced by cold plasma improve the interfacial performance of protein and polysaccharide by changing their residue composition and stereostructure. In the process of modification, hydrophobic groups hidden in protein are exposed and hydrophilic groups are grafted onto the polysaccharide skeleton. Meanwhile, the structural looseness is changed due to the breakage and the formation of bonds. Although successful applications of cold plasma for protein and polysaccharide modification have been demonstrated, it is not enough to characterize the changes at the macro level, and more in-depth studies should be conducted in the future. To improve the interfacial performance of protein and polysaccharide, the mechanism of plasma regulatable modification should be explored, and the accuracy of modification should be enhanced. Highlights: Cold plasma affects the interfacial performance of protein and polysaccharide. Pathways among reactive species of cold plasma were systematically analyzed. The chemical interaction between cold plasma and stabilizers was discussed. Future research trends were proposed.